Nutritional composition and bioactive compounds of a local variety of Vitis vinifera L. cultivated in Morocco - Adil Kalili; Rachida El Ouafi; Abdelghani Aboukhalaf; Kaoutar Naciri; Manal Tbatou; Sara Moujabbir; Abdelmonaim Belahyan; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. The vine is considered one of the most important and popular fruits in the world thanks to its high nutritional value and high fiber content. Objective. This study aim was to evaluate the nutritional composition in a local variety 'Doukkali' grape (Vitis vinifera L.) in the perspective of their suitability for pharmaceutical and agri-food use. Material and methods. The proximate composition and minerals were determined using AOAC methods, the total sugar by HPLC method. The total phenolic compounds using the Folin-Ciocalteu reagent, the total flavonoids using aluminum chloride colorimetric method and tannins by the method of vanillin. Results. The analysis of the raisin of this variety revealed a high carbohydrate content of 61% with high levels of glucose (31.6%), fructose (30.4%), dietary fiber (13.92%) and minerals including potassium (445.50 mg/100 g DM), calcium (193.26 mg/100 g DM), sulfur (171.63 mg/100 g DM), sodium (137.50 mg/100 g DM), phosphorus (99.79 mg/100 g DM), magnesium (54.74 mg/100 g DM) and iron (2.39mg/ g DM). Analysis of bioactive compounds showed significant content of polyphenols varying from 43 to 309.1 mg GAE/g DM, flavonoids from 1.0 to 23.8 mg CEQ/g DM and tannins from 2.5 to 50.45 mg TAE/g DM. Conclusions. The study shows that the local variety of Doukkali grape has an important nutritional potential that can contribute to the nutritional needs and the fight against malnutrition as well as to the dietary diversity of the local population.